Knowledge about COVID-19 and perception of health safety among mexican dental students = Conocimiento sobre COVID-19 y percepción de seguridad en la salud de estudiantes mexicanos de odontología - Olivares Colorado, Jennifer
This study aimed: 1) to investigate sources of information used by students to learn about COVID-19, 2) to investigate levels of knowledge about COVID-19 and about conditions for the treatment of patients during the COVID-19 lockdown, and 3) to evaluate students' perceptions of safety regarding their return to in-person activities at the School of Dentistry. Dental students answered a questionnaire (29 items; n=371) that explored the aims of the study, based on a Likert scale (Cronbach's alpha, 0.778). Data were tested with the Mann-Whitney U test and Kendall's Tau-c. Dental students received information about COVID-19 from the Mexican Health Ministry as their first source (45.28%). Students had good knowledge about the main characteristics of COVID-19, and 59.3% of students had excellent knowledge about the factors relevant to dental treatment of patients. Half of the students said they felt safe regarding a possible return to in-person activities at the dental school, while the other half did not. Statistically significant differences were noted between the students' scholar year and their level of knowledge (P<0.001) and between their perception of safety (very unsafe, unsafe, safe, and very safe) and scholar year (P=0.000). Dental students had good knowledge about COVID-19 and about the dental care for patients during the lockdown. Half of the dental students felt unsafe about a possible return to in-person school activities.